DOI: 10.15368/theses.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Two Test Fixtures to Test the Longitudinal and Transverse Tensile Properties of Small Diameter Tubular Polymers

Abstract: DESIGN AND DEVELOPMENT OF TWO TEST FIXTURES TO TEST THE LONGITUDINAL AND TRANSVERSE TENSILE PROPERTIES OF SMALL DIAMETER TUBULAR POLYMERS Carolyn Rae BerryHundreds of thousands of vascular bypass grafts are implanted in the United States every year, but there has yet to be an ideal graft material to substitute for one's own autologous vessel. Many synthetic materials have been shown to be successful vessel replacements; however, none have been proven to exhibit the same mechanical properties as native vessels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Longitudinal pull to failure testing A custom grip was designed for longitudinal pull-to-failure tests based on Berry et al 38 with modifications. A detailed photographic description of grip assembly is given in Supporting Information, Figure 2.…”
Section: Fiber Diameter Measurementmentioning
confidence: 99%
“…Longitudinal pull to failure testing A custom grip was designed for longitudinal pull-to-failure tests based on Berry et al 38 with modifications. A detailed photographic description of grip assembly is given in Supporting Information, Figure 2.…”
Section: Fiber Diameter Measurementmentioning
confidence: 99%
“…Unfortunately, ePTFE was not available in the material database, however the presence of standard PTFE showed that it exhibits a lower modulus compared to PLGA. This relative difference in elastic modulus values was corroborated by material property results reported in a previous thesis, in which ePTFE and PLGA displayed values of 7.80 and 13.25 MPa respectively when full tubular scaffolds were mechanically tested 141 . The polymers that are reported to have lower Young's modulus values compared to PLGA in This preliminary materials selection phase was simply used to create a short list of potential flexible polymers for future research.…”
Section: Materials Flexibilitysupporting
confidence: 84%
“…The extreme chemical resistance of PTFE is well known, and posed a problem as the primary method of polymer preparation for electrospinning involves dissolution in a solvent. Accordingly, reports of electrospinning with PTFE are not common, and those who have done so successfully incorporated several additional mixing and sintering steps to properly use an emulsified form of PTFE, only to have produced a scaffold with altered morphologies and modulus values of 30.7±2.8 MPa, much stiffer than both the ePTFE tubing and PLGA scaffold tested previously in the BVM lab 141,162,163 .…”
Section: Polytetrafluoroethylene (Ptfe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Each rod could then be pulled in opposite directions to pull the scaffold apart 97 . Future work could use a similar idea for the smaller BBB scaffold in order to prevent disruption of the mechanical properties via sample preparation.…”
Section: Tensile Testing Assessmentmentioning
confidence: 99%